ANALISIS SISTEM PENGAWASAN PERKOPERASIAN OLEH DINAS KOPERASI USAHA KECIL DAN MENENGAH PROVINSI KALIMANTAN BARAT - Mardiana, Mardiana; Asriati, Nuraini; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine the Cooperative Supervision System that has been carried out by the Office of Cooperatives of Small and Medium Enterprises in West Kalimantan Province. The research method used is a case study with a qualitative form of research. Data collection tools used in the form of question sheets, interview guidelines, and documentation. From the results of the study, it is known that (1) the supervision of cooperative compliance of Sinar Mandiri Fortuna has complied with the compliance of the cooperatives both legally, businessly and financially, and transactions have been carried out according to the laws and regulations of the cooperative. Supervision of compliance of cooperative work independently has complied with compliance of cooperatives both legally, businessly and financially, and transactions have been carried out in accordance with cooperative legislation. compliance K2N cooperatives lack compliance with compliance, cooperatives only comply with legal compliance (2) institutional oversight of the fortuna independent cooperative has completed the legality and completeness of the organization. Institutional oversight of cooperative work independently, has completed the legality of cooperatives and the completeness of cooperative organizations. Oversight of K2N cooperative institutions, does not complete the legality and completeness of the organization. (3) supervision of the savings and loan cooperative fortune rays, the collection of funds sourced from members and given to the members Supervision of cooperative work independently, the collection of funds sourced from members and given to members. Supervision of K2N cooperatives, raising funds sourced from members and given to members.Â Keywords: Compliance Supervision, Institutional Supervision, Savings and Loan Â Supervision